1999
DOI: 10.1021/jp983734v
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Charge Transport in Anisotropic Layers of a Phthalocyanine Polymer

Abstract: Solid samples of phthalocyaninato-polysiloxanes (PcPS) have been analyzed by electrical dark conductivity experiments and by pulse-radiolysis time-resolved microwave conductivity (PR-TRMC) measurements. The in-plane conductivity of anisotropic PcPS Langmuir−Blodgett assemblies on gold surface-comb electrodes reveals an ohmic dependence at low voltages followed by a space-charge-limited current regime at higher electric fields. The conductivity displays a close to Arrhenius-type temperature dependence, with act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 37 publications
4
22
0
Order By: Relevance
“…19 The results of these measurements are summarized in Table I. Similar studies of dc conductivity on IMEs have been reported by Neher and coworkers for rod-like silicon phthalocyanine polymers, [12][13][14] and in our own preliminary work for Pc 1. 20 Relatively thick (28 bilayers) multilayer thin films of Pcs 1 and 1' and 28 monolayer films of Pc 2 were deposited onto two IMEs oriented orthogonal to each other during the horizontal deposition process, producing comparable Pc thin films from the same Langmuir layer with parallel and perpendicular orientations of the Pc column rod axes with respect to the legs of the microcircuit (inset of Fig.…”
Section: A DC Conductivities For Pcs 1 and 1'supporting
confidence: 79%
See 2 more Smart Citations
“…19 The results of these measurements are summarized in Table I. Similar studies of dc conductivity on IMEs have been reported by Neher and coworkers for rod-like silicon phthalocyanine polymers, [12][13][14] and in our own preliminary work for Pc 1. 20 Relatively thick (28 bilayers) multilayer thin films of Pcs 1 and 1' and 28 monolayer films of Pc 2 were deposited onto two IMEs oriented orthogonal to each other during the horizontal deposition process, producing comparable Pc thin films from the same Langmuir layer with parallel and perpendicular orientations of the Pc column rod axes with respect to the legs of the microcircuit (inset of Fig.…”
Section: A DC Conductivities For Pcs 1 and 1'supporting
confidence: 79%
“…Many liquid crystalline discotic mesophase materials self-organize from common solvents into coherent columnar, rod-like aggregates, and have become of interest as potential solution-processed molecular electronic materials. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Side-chain modified phthalocyanines, porphyrins, hexabenzocoronenes, and triphenylenes have been created that show reasonable liquid crystalline (LC) transition temperatures (K → D h ) and can be readily processed into thin films. The side chains surrounding the discotic molecular core help control self-organization into these rod-like columns, and because of their closepacking and electrically insulating nature, their presence may eventually provide for dense lateral integration of organic field-effect transistor (OFET) devices, preventing significant electrical cross-talk between adjacent columns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that comparable combinations of hydrophobic and hydrophilic channel walls and upper and lower surfaces can be used to create useful patterns of a wider range of hydrophobic monomeric and polymeric materials, and that the lCP-EP approach can be extrapolated to submicrometer dimensions. (2,3,9,10,16,17,23,24-Oktakis((2-benzyloxy)-ethoxy)phthalocyaninato) copper (1) was synthesized as reported previously [51]. Solutions of 1 were prepared using high-pressure liquid chromatography (HPLC) grade chloroform 99.9 % (Aldrich).…”
Section: Discussionmentioning
confidence: 99%
“…[15±26] We have recently shown that Pcs with benzyl-terminated ethylene oxide chains (i.e., (2,3,9,10,16,17,23,24-oktakis((2-benzyloxy)ethoxy)phthalocyaninato) copper, 1 (Fig. 1a)) adopt cofacial aggregate geometries in dilute solution.…”
Section: Introductionmentioning
confidence: 99%